Evaluasi Pelaksanaan Penguatan SDM Program Sekolah Penggerak di Sekolah Menengah Pertama dengan Model CIPPO - Rahmat Dhoni Wiryatmo; Ade Iriani; Marinu Waruwu (Kelola: Jurnal Manajemen Pendidikan, 2023)
This study aims to evaluate: context, input, process, product, and outcome in the implementation of strengthening human resources in the Program Sekolah Penggerak at SMPN 1 Bringin. This type of research is descriptive evaluative to find out the description of a phenomenon and or its relationship with other phenomena. Data collection techniques using interviews, observation and documentation studies. Data validation using triangulation. Data analysis includes data reduction, presentation, and verification. The results of this study indicate: (1) Context. Teachers’ competencies is low, students character is not appropriate, and the school's cultural climate is less solid, and program improvements are needed; (2) Inputs. PSP with the Merdeka curriculum is the answer regarding a curriculum model that is in line with the development of the world of education where the readiness of stakeholders is well coordinated, (3) Process. Starting with program preparation, facilitation and implementation, mentoring, evaluation and reflection on all activities. (4) Products. Teachers are increasingly mastering digital devices, schools are equipping digital-based infrastructure to support learning activities, co-curricular, intra-curricular and extra-curricular activities are going well, at the end of the strengthening project a "Pagelaran" is held in the form of art performances and student product exhibitions, the internal condition of schools has built a climate culture good school. (5) the outcome, strengthening human resources in the PSP shows that the results of the performance of educators and education staff have increased where teachers are able to complete tasks with full responsibility, use new learning paradigms and learning differentiation.